An evidence of local structural disorder across spin-reorientation transition in DyFeO3: an extended x-ray absorption fine structure (EXAFS) study. (5th June 2019) - Panchwanee, Anjali; Schiesaro, Irene; Mobilio, Settimio; Reddy, S Shravan Kumar; Meneghini, Carlo; Welter, Edmund; Raghavendra Reddy, V
Abstract: The present work is aimed at exploring the local atomic structure modifications related to the spin reorientation transition (SRT) in DyFeO3 orthoferrite exploiting x-ray absorption fine structure (XAFS) spectroscopy. For this purpose we studied by XAFS the evolution of the local atomic structure around Fe and Dy as function of temperature (10–300 K) in a DyFeO3 sample having the SRT around 50–100 K. For sake of comparison we studied a YFeO3 sample having no SRT. The analysis of the extended region has revealed an anomalous trend of Fe–O nearest neighbour distribution in DFO revealing (i) a weak but significant compression with increasing temperature above the SRT and (ii) a peculiar behavior of mean square relative displacement (MSRD) [ ] of Fe–O bonds showing an additional static contribution in the low temperature region, below the SRT. These effects are absent in the YFO sample supporting these anomalies related to the SRT. Interestingly the analysis of Dy L 3 -edge data also reveal anomalies in the Dy–O neighbour distribution associated to the SRT, pointing out a role of magnetic Re ions across . These results point out micro-structural modification at both Fe and Dy sites associated to the magnetic transitions in DFO, it can be stated in general terms that such local distortions across and magnetic Re 3+ may be present in other orthoferrites exhibiting multiferroic nature.